Ethnicity/culture modulates the relationships of the haptoglobin (Hp) 1‐1 phenotype with cognitive function in older individuals with type 2 diabetes. (21st September 2015) - Guerrero‐Berroa, Elizabeth; Ravona‐Springer, Ramit; Heymann, Anthony; Schmeidler, James; Hoffman, Hadas; Preiss, Rachel; Koifmann, Keren; Greenbaum, Lior; Levy, Andrew; Silverman, Jeremy M.; Leroith, Derek; Sano, Mary; et al.
Abstract : Objective: The haptoglobin (Hp) genotype has been associated with cognitive function in type 2 diabetes. Because ethnicity/culture has been associated with both cognitive function and Hp genotype frequencies, we examined whether it modulates the association of Hp with cognitive function. Methods: This cross‐sectional study evaluated 787 cognitively normal older individuals (>65 years of age) with type 2 diabetes participating in the Israel Diabetes and Cognitive Decline study. Interactions in two‐way analyses of covariance compared Group (Non‐Ashkenazi versus Ashkenazi Jews) on the associations of Hp phenotype (Hp 1‐1 versus non‐ Hp 1‐1) with five cognitive outcome measures. The primary control variables were age, gender, and education. Results: Compared with Ashkenazi Jews, non‐Ashkenazi Jews with the Hp 1‐1 phenotype had significantly poorer cognitive function than non‐Hp 1‐1 in the domains of Attention/Working Memory ( p  = 0.035) and Executive Function ( p  = 0.023), but not in Language/Semantic Categorization ( p  = 0.432), Episodic Memory ( p  = 0.268), or Overall Cognition ( p  = 0.082). After controlling for additional covariates (type 2 diabetes‐related characteristics, cardiovascular risk factors, Mini‐mental State Examination, and extent of depressive symptoms), Attention/Working Memory ( p  = 0.038) and Executive Function ( p  = 0.013) remained significant. Conclusions: Older individuals from specific ethnic/cultural backgrounds with the Hp 1‐1 phenotype may benefit more from treatment targeted at decreasing or halting the detrimental effects of Hp 1‐1 on the brain. Future studies should examine differential associations of Hp 1‐1 and cognitive impairment, especially for groups with high prevalence of both, such as African–Americans and Hispanics. Copyright © 2015 John Wiley & Sons, Ltd.